High-speed cutting with involute blades: Experimental research on cutting forces. (March 2021) - Bremer, F.; Matthiesen, S.
Abstract: Industrial slicing is a common high-speed food cutting process to produce consumer-ready slices. High productivity is achieved by using curved blades that allow a continuous process. However, experimental research to validate theoretical models on the complex interactions of food and blade, which determine the cutting forces, are missing. An industrial slicing machine has been equipped with load cells to measure force profiles during slicing. The profiles of two types of processed meat at rotational blade speeds of 600 rpm and 1200 rpm are analyzed. Although both foods show a large variance in the force profiles, a velocity dependence of the forces can be shown. The otherwise irregular curvatures point to strong contributions of friction and deformation. We compare the measurement data with a fracture energy model of cutting forces for industrial slicing applications. The results show, that the model is inadequate. We conclude that the model would improve by including deformation and friction in the model. Highlights: Variance and magnitude of cutting forces increase with cutting speed Significant contributions of friction and deformation to cutting forces No cut initiation phase was observed for cutting with an involute blade Compression of the uncut food influences the process forces in industrial slicing